Diet and Chronic Kidney Disease. (15th November 2019) - Kramer, Holly
ABSTRACT: Kidney disease affects almost 15% of the US population, and prevalence is anticipated to grow as the population ages and the obesity epidemic continues due to Western dietary practices. The densely caloric Western diet, characterized by high animal protein and low fruit and vegetable content, has fueled the growth of chronic diseases, including chronic kidney disease. The glomerulus or filtering unit of the kidney is very susceptible to barotrauma, and diets high in animal protein impede the glomerulus' ability to protect itself from hemodynamic injury. High animal protein intake combined with low intake of fruits and vegetables also leads to a high net endogenous acid production requiring augmentation of ammonium excretion in order to prevent acidosis. This higher workload of the kidney to maintain a normal serum bicarbonate level may further exacerbate kidney disease progression. This article reviews the potential mechanisms whereby several key characteristics of the typical Western diet may impact kidney disease incidence and progression. Reducing animal protein intake and egg yolk and increasing intake of fruits and vegetables and fiber may prevent or delay end-stage renal disease, but few clinical trials have examined vegetarian diets for management of chronic kidney disease. More research is needed to determine optimal dietary patterns for the prevention of kidney disease and its progression.